STRESS ANALYSIS OF SUSPENSION SYSTEM BY USING COMPOSITE MATERIAL UNDER THE STATIC LOAD CONDITION USING FEA - Nisar Shaikh1, Sanjay Pawar2 (International Journal of Innovations in Engineering Research and Technology, 2022)
In order to conserve natural resources and economize energy, weight reduction has been the main focus of automobile manufacturer in the present scenario. Weight reduction can be achieved primarily by the introduction of better material, design optimization and better manufacturing processes.The present project is focused on quantifying the stress & deflection analysis using the existing (default) metal leaf springs and then by replacing them with carbon fiber springs. The project gives a brief look on the suitability of composite leaf spring on vehicles and their advantages. Efforts have been made to check the load-deflection of composite leaf spring to that of steel leaf spring. The achievement of bending stresses & weight reduction with adequate improvement of mechanical properties has made composite a very replacement material for convectional steel. Material is selected upon the cost and strength factor. The objective is to present, modeling and analysis of composite mono leaf spring and compare its results. Modeling is done using CATIA and Analysis is carried out by using ANSYS 14.0 software for better understanding. From the comparative study, it is seen that bending stresses in composite material is reduced as compared to conventional steel leaf spring & it is visible upto 10.34 % reduction observed in bending stresses which is desirable for leaf spring of vehicle & also it has been noticed that , the composite material leaf spring is deflect more as compared to the steel leaf spring i.e upto 9.27 % more, so that composite material leaf spring lower the spring rate as compared to the steel leaf spring. Spring rate is amount of weight required to deflect a spring one inch. The lower the spring rate , softer the spring. Therefore, smoother thre ride.